(untitled) (Conference on English Language Teaching, 2023)
Looking at how language functions differently when it is used by specific people at a certain time and agenda, this study aims to see how a specific political leader influences the audience by using certain words and gestures to engage with. The data were taken from Jacinda Ardern’s final speech in April 2023 in the parliament on YouTube as she resigned from her position as New Zealand’s Prime Minister. This study applied a descriptive-qualitative study by using qualitative library research and document analysis for the data collection. The data were analyzed using Fairclough’s (2001) theory on Synthetic Personalization and Van Leeuwen’s (2008) Social-semiotic Multimodal analysis. The findings show Jacinda Ardern used synthetic personalization to build intimacy, to engage with the audience, and to create a simulated personal relationship with the audience by telling her personal story, using specific vocabularies such as you, we, and our to build a deeper relationship with the audience resulting in the audience getting immersed during her speech and a mass standing ovation. Social-semiotic shortens the distance between speaker and audience by creating social interaction by showing gestures, eye distance, and gaze.